Spidey and his amazing friends. Spidey saves the day - Behling, Steve (Los Angeles : Marvel, 2021)
Everyone's favorite webslinger and his superhero friends team up with the Hulk and Ms. Marvel to battle such villains as Green Goblin and Doc Ock.
Spidey surprise -- Monkeying around! -- Helping of Hulk -- Lost and found -- Attack of the green giggles!
Based on the episodes 'Spidey Surprise': Baljeet Rai, 'Monkeying Around': Ken Kristensen, 'A Helping of Hulk': Baljeet Rai, 'Lost and Found': Henry Gifford, 'Attack of the Green Giggles!': Henry Gifford.
5 amazing adventure stories!--Front cover.
1.8
K-3
410L
Keywords: Spider-Man -- (Fictitious character) -- Juvenile fiction; Hulk -- (Fictitious character) -- Juvenile fiction; Marvel, -- Ms. (Fictitious character) -- Juvenile fiction; Green Goblin -- (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Spider-Man -- (Fictitious character) -- Fiction; Superheroes -- Fiction; Supervillains -- Fiction; Superhero fiction; Adaptations; Readers (Elementary)